52 FGD1 Splice Variant in Clear Cell Renal Cell Carcinoma is a Novel Biomarker for Inferior Clinical Outcomes and Development of Brain and Bone Metastases - Kendrick Yim; Alyssa Obermayer; Kapil Avasthi; Youngchul Kim; Alex Soupir; Mitchell Hayes; Andrew Chang; Joshua Davis; Roy Elias; Nirmish Singla; Michelle Churchman; Daniel Grass; et al. (The Oncologist, 2026)
Abstract Background Clear cell renal cell carcinoma (ccRCC) lacks reliable tissue biomarkers. Recurrent splice variants (SVs) in ccRCC offer biomarker potential given stable molecular alterations and disease specificity. The novel FYVE, RhoGEF and PH domain protein 1 SV (FGD1-SV) has recently been identified and significantly associated with worse survival in ccRCC. Our study aims to validate clinical outcomes for tumors with FGD1-SV, investigate metastatic organotropism, and explore the feasibility of a novel multiplex RT-PCR-based sequencing assay for FGD1-SV among ccRCC patients. Methods FGD1-SV expression was evaluated in two independent cohorts. A prospective institutional cohort of 81 patients with localized or locally advanced ccRCC undergoing nephrectomy was analyzed using a novel multiplex RT-PCR-based sequencing assay. External validation was performed using the Oncology Research Information Exchange Network (ORIEN) cohort including 1727 patients with ccRCC (793 localized, 622 locally advanced, and 312 metastatic) with bulk RNA sequencing data. Associations with clinicopathologic features and treatments were assessed using correlation and group comparisons. Survival outcomes were evaluated using Kaplan–Meier analysis and Cox proportional hazards models. Results In the prospective cohort, higher FGD1-SV expression was associated with larger tumor size (r = 0.44, p < 0.0001), advanced stage (p < 0.001), higher nuclear grade (p = 0.002). Detectable FGD1-SV expression was associated with developing metastasis (HR 10.9, 95%CI:2.2–53.3) and inferior metastasis-free survival (log-rank p = 0.003). Among patients treated with adjuvant pembrolizumab, FGD1-SV positivity identified individuals with inferior recurrence-free survival (p = 0.011). In the ORIEN cohort, FGD1-SV positivity was associated with worse overall survival (HR 1.55, 95%CI:1.05–2.29) and decreased metastasis-free survival (HR 1.55, 95%CI:1.15–2.09) in locally advanced disease and worse overall survival in metastatic disease (HR 1.82, 95%CI:1.34–2.47). FGD1-SV positivity was associated with increased risk of brain (HR 2.30, 95%CI:1.06–5.00) and bone metastases (HR 2.32, 95%:CI1.32–4.07). Among metastatic patients who received single agent pembrolizumab (n = 143), FGD1-SV positivity was associated with worse overall survival (HR 2.3, 95%CI 1.00–5.35). The prevalence of FGD1-SV positivity increased with advancing stage (p-trend=0.0001), and expression was highest in brain and bone metastases (p = 0.0049). Limitations include the retrospective nature of the validation cohort. Conclusions FGD1-SV expression detected through a RT-PCR-based sequencing assay identifies ccRCC tumors with aggressive biologic features and inferior clinical outcomes. Enrichment of FGD1-SV in brain and bone metastases suggests a role in metastatic organotropism and highlights its potential as a biomarker for risk-adapted surveillance and possibly treatment strategies. DOD CDMRP Funding no